Analisis Kerjasama Gabungan Kelompok Tani Dalam Meningkatkan Kesejahteraan Petani Desa Perapakan Kecamatan Pemangkat - Indah Sari; Wahab; Ahmad Yasir (Hikamatzu | Journal of Multidisciplinary, 2026)
This study analyzes the cooperation of farmer group associations, locally known as Gapoktan, in improving farmer welfare in Perapakan Village, Pemangkat District. The study responds to farmers difficulties in accessing production inputs, technical guidance, agricultural assistance, and coordination across farmer groups. This article applies a descriptive qualitative approach by reviewing field data derived from observation, interviews, documentation, and secondary data from previous research on Gapoktan Mitra Usaha in Perapakan Village. Data were analyzed through reduction, display, and conclusion drawing. The findings show that Gapoktan Mitra Usaha functions as a coordination forum for 31 farmer groups with approximately 625 members. Cooperation is implemented through shared goal setting, communication with farmer group leaders, technical guidance, extension activities, distribution of fertilizer, improved seeds, and pesticides, as well as support in solving cultivation problems. These activities reduce production cost burdens, improve farmers knowledge, strengthen rice cultivation practices, and contribute to better quantity and quality of harvest. However, welfare improvement remains affected by seasonal conditions, water availability, pests, and the fairness of input distribution. This article argues that Gapoktan cooperation is an important instrument for strengthening farmer institutions, but its effectiveness requires fair governance, regular coaching, and a more measurable productivity evaluation system.